Additional costs of FAS and PFAS learners in the classroom: An estimate for public primary schools in the Western Cape - Makin, Emma (Department of Public Health and Family Medicine, 2018)
Background: The Western Cape province of South Africa has the highest recorded prevalence rates of Fetal Alcohol Spectrum Disorders (FASD) in the world. In the last decade rates of fetal alcohol syndrome (FAS) and partial fetal alcohol syndrome (PFAS) prevalence of 68.0 - 89.2 per 1000 (May et al., 2007), 67.2 per 1000 (Urban et al., 2008), and 59.3 - 91.0 per 1000 (May et al., 2013) have been published after research was conducted in towns in the Western Cape (WC). Educating learners with FASD is a challenge as a result of the large range of cognitive impairments associated with heavy prenatal alcohol exposure. Determining a burden of cost to the education system may be one way to motivate for the development of prevention and intervention strategies. Methods: I designed questionnaires that were distributed to the educator and principal of a cohort of learners including learners with FAS and PFAS. Data were collected on educational impacts of variables associated with educator time use. Additional costs as a result of the use of educator's time by learners with FAS/PFAS were scaled up using risk differences and published statistics to reflect a cost burden to the WC Education Department. Results: The additional cost burden of disruptions caused by learners with FAS and PFAS for the WC Education Department is USD 7,010,166 in educator time for one academic year. The additional burden for learners with FAS/PFAS requiring additional assistance with lesson content to the WC is USD 5,754,885 in educator time for one academic year. The additional cost burden of public primary school learners with FAS/PFAS who had repeated a year of schooling was USD 3,876,565 in educator time based on 2012 salaries. Conclusions: These findings indicate that there is a large burden of cost to the education system when educator time is viewed as an economic input in education. Efforts need to be directed towards prevention programs to reduce the prevalence of learners with FAS/PFAS in the classroom. Educator training programs must be created to ensure that educators are equipped to manage the challenges posed by learners with FAS/PFAS in the classroom.